Women writing novels on art: ekphrasis in twenty-first century fiction - Behluli, S (2021)
Twenty-first century literature is marked by a number of authors who engage with visual art in their work, five prime examples being Donna Tartt, Amy Sackville, Hanya Yanagihara, Claire Messud and Siri Hustvedt. Their novels create imaginative spaces where word meets image and where reading blends into seeing. Through ‘ekphrasis’, a descriptive mode of evoking visual art that goes back to Classical Antiquity, these novels disturb automatised patterns of looking, reading, thinking and judging, and encourage a more attentive, critical and ultimately also ethical relationship to contemporary culture. Writing about art is particularly fruitful for women because, as Hilary Fraser puts it, it “enable[s them] to rehearse with greater freedom issues relating not only to the gender politics of their profession and the writing of art’s histories, but to sexuality, visuality and intersubjectivity.” (42) My reading of five contemporary novels – ‘The Goldfinch’ (2013), ‘Painter to the King’ (2018), ‘A Little Life’ (2015), ‘The Woman Upstairs’ (2013) and ‘The Blazing World’ (2014) – further explores these issues by focusing on the nexus of the novel, visual art, ekphrasis and gender. Given their expansive intertextual and re-inscriptive strategies, I analyse these novels alongside other works written by men and women from the nineteenth century onward.